Genetic Characterization of a blaVIM–24-Carrying IncP-7β Plasmid p1160-VIM and a blaVIM–4-Harboring Integrative and Conjugative Element Tn6413 From Clinical Pseudomonas aeruginosa - Zeng, Lijun; Zhan, Zhe; Hu, Lingfei; Jiang, Xiaoyuan; Zhang, Yanjun; Feng, Jiao; Gao, Bo; Zhao, Yuee; Yang, Wenhui; Yang, Huiying; Yin, Zhe; Zhou, Dongsheng (Frontiers in Microbiology, 2019)
To deal with a detailed genetic characterization of a blaVIM-24-carrying IncP-7β plasmid p1160-VIM and a blaVIM-4-harboring integrative and conjugative element (ICE) Tn6413 from clinical Pseudomonas aeruginosa. P. aeruginosa 1160 and 6762 were subjected to high-throughput genome sequencing. The complete nucleotide sequence of p1160-VIM from the 1160 isolate and that of the 6762 chromosome carrying Tn6413 were determined, and then comparison of p1160-VIM or Tn6413 with related sequences was performed. A replicon-based scheme was proposed to subgroup IncP-7 into IncP-7α and IncP-7β. p1160-VIM belonged to the IncP-7β group, and carried Tn6392 and Tn6393. Tn6413 was a large chromosome-borne ICE carrying Tn6403. Tn6392, Tn6393 and Tn6403 were gen-erated from integration of blaVIM-24-carrying In1394, In1395 and blaVIM-4-barboring In1443 into prototype Tn3-family unit transposons Tn5563, Tn1403 and Tn6346, respec-tively. This is the first report of a blaVIM-24-carrying P. aeruginosa isolate and a fully se-quenced IncP-7 resistance plasmid. This study presents three novel insertion sequences ISpa75, ISpa79 and ISpa82, three novel integrons In1394, In1395 and In1443, three novel unit transposons Tn6392, Tn6393 and Tn6403, and one novel ICE Tn6413, as observed in P. aeruginosa 1160 or 6762.